Formulation and Characterization of Gels of Telang Flower Extract (Clitoria Ternatea L) with Variations of Carbopol Concentration and Antioxidant Activity Test Using DPPH Methods - Nurwaini, Setyo; Fatimah, Mutiara Nurul (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Telang flower (Clitoria ternatea L) has antioxidant activity. Formulation in gel form provides convenience in the use of telang flower extract. This study aims to determine the effect of carbopol as a gelling agent on the physical properties of the gel and to determine the antioxidant activity of telang flower extract gel. Telang flower extract was obtained by maceration method. The gel was formulated with 3 variations of carbopol concentration, namely 0.5%, 1% and 2%. Characterization of Clitoria ternatea L. gel includes: organoleptic, homogeneity, pH, viscosity, spreadability and stickiness. Antioxidant activity test of telang flower (Clitoria ternatea L) using DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The gel formulation of telang flower extract (Clitoria ternatea L.) from 3 formulas met the requirements. Gel with 2% carbopol concentration was the gel with the best characteristics: pH 5.82; viscosity 2,666 cP; spreadability 4.33 cm; stickiness 2.2 s. The Antioxidant activity test of telang flower extract gel showed strong category with an IC50 value of 97.72 ppm. Carbopol has an influence on the physical properties of telang flower extract (Clitoria ternatea L) gel and strong antioxidant activity of bay flower extract gel.